Burkholderia pseudomallei no estado do Ceará : caracterização de reservárias - Rolim, Dionne Bezerra (2009)
Melioidosis, a disease caused by the Gram-negative bacteria Burkholderia pseudomallei, is endemic in southeast Asia and in Australia and shows a sporadic distribution in other parts of the world. The disease has been described in the Americas, it is an emergent illness in Brazil, as human cases are well documented in Ceará state. This research aims to better understand the ecology of the bacteria. The study was carried out by means of an environmental search for B. Pseudomallei in the ground of the cities Tejuçuoca and Banabuiú and by a epidemiological surveillance on the local rural population. For the environmental study, soil samples were collected monthly from the surface down to 40 cm depth from January to December 2007. Five sampling sites in each municipality were chosen near to the homes of people who had melioidosis. For the serological study, serum samples of 321 inhabitants of those areas were collected, and an inquiry was taken that included data about demography, previous illnesses and activities related to exposition to water and soil. Serological titers were determined by means of an immunoenzymatic test, using microplates adsorbed with filtered antigen of B. Pseudomallei. The bacteria was found in the soil of Tejuçuoca and Banabuiú municipalities in 4.3% (26/600) of the samples. Both regions show similar geoclimatic and environmental aspects, such as soil and vegetation, rainfall index, and temperatures. Detection of B. Pseudomallei occurred in tropical semi-arid climate, with low annual pluviometric index and a shrubby “caatinga” vegetation, showing an influence of local factors enabling the survival and multiplication of the microorganism. Epidemiological surveillance showed 51.27% (161/327) for the IgM isotype and 58.49% (186/317) for IgG isotype. Frequency of IgM titers was higher among children than adults, while IgG frequency raised with age. There was a significant association between agricultural occupations and IgM (44.15%, p<0.005) and IgG titers (44.15%, p<0.005) and between construction workers and IgG titers (84.6%, p=0.005). Most samples with high titers showed reactivity to the 33 and 45 kD bands, which correspond to the polysaccharide O of the liposaccharide chain of the bacteria.